Karakteristik Fisik dan Mekanik Pasta Fill Sebagai Material Backfill Pada Proses Ground Support Di Underground Kencana, PT. Nusa Halmahera Minerals, Provinsi Maluku Utara - Hafizh Murtadho; Yuliadi; Yunus Ashari (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Nusa Halmahera Minerals is a mining company engaged in the gold mining business located in Gosowong, North Maluku. Mining is carried out with Open Pit Mining System and Underground Mining System using Open Pit Mini ng and Underhand Cut and Fill types. Geotechnical conditions in the Underground Mine are the main consent for the company by considering the safety of workers. There are several factors that can affect tunnel stability, including the condition of rock lithology, rock deformation, and groundwater conditions that interfere with ground support. Based on the actual situation in the field, there are still several active headings that are disturbed due to excessive groundwater which makes the mining cycle hampered due to the rehabilitation process, the presence of groundwater affects the condition of strengthening ground support in pasta fill (backfill) so that the tunnel has the potential to experience squeezing or shrinkage and rock collapse / collapse caused by load stress on rocks due to mining activities, Based on the results of observations and calculations, the 24% paste fill mix design conditions decreased in strength to 0.771 Mpa, with a Strength Factor value of 0.95 - 6. And get a total displacement value of 0.02 - 0.38 m. Geotechnic Monitoring Lidar validation states that there is movement in the roof and wall area in the K2-16 Sill area with a velocity value of 0.151 mm per day. Mix design recommendations affect the strengthening of ground support so as to maintain an optimal mining cycle and achieve the company's target. Abstrak. PT. Nusa Halmahera Minerals merupakan perusahaan tambang yang bergerak di bidang usaha pertambangan emas yang berlokasi di Gosowong, Maluku Utara. Penambangan dilakukan dengan Sistem Tambang Terbuka dan Sistem Tambang Bawah Tanah menggunakan jenis Open Pit Mining dan Underhand Cut and Fill. Kondisi geoteknik pada Tambang Bawah Tanah merupakan consent utama bagi perusahaan dengan mempertimbangkan keselamatan para pekerja. Terdapat beberapa faktor yang dapat mempengaruhi kestabilan terowongan, diantaranya kondisi lithology batuan, adanya deformasi batuan, dan kondisi air tanah yang mengganggu terhadap ground supporting. Berdasarkan keadaan aktual di lapangan masih terdapat beberapa heading aktif yang terganggu akibat adanya air tanah yang berlebih sehingga membuat siklus penambangan terhambat akibat adanya proses rehab, adanya air tanah berpengaruh terhadap kondisi penguatan ground support pada pasta fill (backfill) sehingga terowongan berpotensi mengalami squeezing atau penyusutan dan runtuhnan batuan/collapse yang diakibatkan oleh load stress pada batuan akibat aktivitas penambangan tersebut. Berdasarkan hasil pengamatan dan perhitungan kondisi mix design pasta fill 24% mengalami penurunan kekuatan menjadi 0,771 Mpa, dengan nilai Strength Factor sebesar 0.95 – 6. Dan mendapatkan nilai total displacement sebesar 0.02 – 0.38 m. Validasi Geotechnic Monitoring Lidar menyatakan adanya pergerakan pada area roof dan juga wall di area K2-16 Sill dengan nilai velocity 0.151 mm per harinya. Rekomendasi mix design berpengaruh terhadap penguatan ground support sehinga mampu menjaga siklus penambangan yang optimal dan mencapai target dari perusahaan.